Tourette's syndrome in famous musicians - Camargo,Carlos Henrique F. (2015)
Tourette's syndrome (TS) is defined as a disorder characterized by multiple motor tics and at least one vocal tic that have lasted for not less than one year. It is a relatively complex neurobehavioral disorder, in which patients may present with coexistent attention deficit hyperactivity disorder, obsessive-compulsive disorder or other behavioral comorbidities. The musical genius Wolfgang Amadeus Mozart (1756-1791) and the rock star Kurt Cobain (1967-1994) may both have suffered from TS, and some contemporary musicians have had their clinical condition confirmed as TS. Our hypothetical diagnosis of TS in Mozart and Cobain is based on the presence of tics and psychiatric comorbidities. In contemporary musicians, such as Michael Wolff, Nick Van Bloss and James Durbin, TS has often only been diagnosed after a considerable delay. This delay in diagnosis and the controversies surrounding the clinical case of Mozart show how difficult a confirmatory diagnosis of this complex disease is.